2012
DOI: 10.1242/dev.084053
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for karyoplasmic homeostasis during endoreduplication and a ploidy-dependent increase in gene transcription during tomato fruit growth

Abstract: SUMMARYEndopolyploidy is a widespread process that corresponds to the amplification of the genome in the absence of mitosis. In tomato, very high ploidy levels (up to 256C) are reached during fruit development, concomitant with very large cell sizes. Using cellular approaches (fluorescence and electron microscopy) we provide a structural analysis of endoreduplicated nuclei at the level of chromatin and nucleolar organisation, nuclear shape and relationship with other cellular organelles such as mitochondria. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 62 publications
9
117
0
1
Order By: Relevance
“…To test this, overall RNA Pol II transcriptional activity was determined by quantifying the proportion of elongating (phosphorylated Serine 2, S2P) versus poised (nonphosphorylated, NP) RNA Pol II forms in individual cotyledon nuclei isolated from dark-and light-grown seedlings (51,52). Because ploidy levels significantly increase during cotyledon de-etiolation (29) and are positively correlated with the amount of RNA Pol II (53,54), measurements of S2P and NP RNA Pol II signals were obtained separately for the nuclei of each ploidy class (Fig. S6).…”
Section: Light Signaling Components Control Nuclear Architecture Reormentioning
confidence: 99%
“…To test this, overall RNA Pol II transcriptional activity was determined by quantifying the proportion of elongating (phosphorylated Serine 2, S2P) versus poised (nonphosphorylated, NP) RNA Pol II forms in individual cotyledon nuclei isolated from dark-and light-grown seedlings (51,52). Because ploidy levels significantly increase during cotyledon de-etiolation (29) and are positively correlated with the amount of RNA Pol II (53,54), measurements of S2P and NP RNA Pol II signals were obtained separately for the nuclei of each ploidy class (Fig. S6).…”
Section: Light Signaling Components Control Nuclear Architecture Reormentioning
confidence: 99%
“…These two probes were used in parallel not only to explore complementary spectral domains but also to appreciate nonspecific binding (to lipids and waxes), which tends to be higher with DiOC 6 (5), even though it is a potential-sensitive dye, than with MitoTracker Red (Bourdon et al, 2012). Using confocal microscopy, we clearly identified active mitochondria in Col-0 leaf mesophyll ( Figure 4A) and epidermal ( Figure 4B) cells.…”
Section: The Cls Mutation Affects Mitochondrial Structure and Functionmentioning
confidence: 99%
“…Furthermore, endoreplication is believed to be an important trigger for cell and organ growth, because cell size is frequently correlated with the DNA ploidy levels (Melaragno et al, 1993;De Veylder et al, 2011), although such a relationship is not always observed (Beemster et al, 2002). In tomato (Solanum lycopersicum), increased ploidy levels are correlated with increased levels of rRNA and protein synthesis per-nucleus, indicating increased metabolism to support cell growth (Bourdon et al, 2012). Endoreplication has also been demonstrated to instruct cell fate, as observed for Arabidopsis trichomes .…”
mentioning
confidence: 99%